New and interesting Portuguese Lepidoptera records from 2016 (Insecta: Lepidoptera) - M. F. V. Corley; J. Rosete; A. R. Gonçalves; V. Mata; J. Nunes; P. Pires (SHILAP, 2018)
32 species are added to the Portuguese Lepidoptera fauna, mainly as a result of fieldwork undertaken by the authors and others in 2016. In addition, second and third records for the country, new province records and new food-plant data for a number of species are included. A summary of recent papers affecting the Portuguese fauna is included